2013
DOI: 10.1186/1477-7525-11-197
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implant treatment on oral health related quality of life in a private dental practice: a prospective cohort study

Abstract: BackgroundVery few studies on the impact of implant therapy on Oral Health Related Quality of Life (OHRQoL) in partially edentulous patients have been published.AimThis study aimed at analysing the improvement of OHRQoL of patients who underwent dental implant treatment using the “functional”, “psychosocial” and “pain and discomfort” categories of the Geriatric Oral Health Assessment Index (GOHAI).MethodsWithin a prospective cohort of patients rehabilitated with Straumann dental implants, the OHRQoL of 176 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
(46 reference statements)
3
46
0
2
Order By: Relevance
“…25 The results of the present study showed that after IMO treatment, patients reported significant improvements (p < 0.05) in the psychosocial and pain and discomfort domains. The increase in the psychosocial domain highlights the fact that the OHRQoL of patients improved after IMO treatment, as demonstrated in previous studies.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…25 The results of the present study showed that after IMO treatment, patients reported significant improvements (p < 0.05) in the psychosocial and pain and discomfort domains. The increase in the psychosocial domain highlights the fact that the OHRQoL of patients improved after IMO treatment, as demonstrated in previous studies.…”
Section: Discussionsupporting
confidence: 48%
“…The increase in the psychosocial domain highlights the fact that the OHRQoL of patients improved after IMO treatment, as demonstrated in previous studies. 25 Although the global score increased after IMO installation, there was no significant difference between the initial and final scores.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dental implants support either a fixed or a removable prosthesis and can provide a significant benefit to partially or fully edentulous patients [20]. The success or failure of oral treatment using conventional dentures depends on many factors, including the practitioner's technical skills and unfavorable oral conditions [21].…”
Section: Introductionmentioning
confidence: 99%